Pathogenesis and vertical transmission of a transplacental rat cytomegalovirus - Loh, Hwei San; Mohd Lila, Mohd Azmi; Abdul Rahman, Sheikh Omar; Kiew, Lik Jun (Springer, 2006)

(untitled)
Background Cytomegalovirus (CMV) congenital infection is the major viral cause of well-documented birth defects in human. Because CMV is species-specific, the main obstacle to developing animal models for congenital infection is the difference in placental architecture, which preludes virus transmission across the placenta. The rat placenta, resembling histologically to that of human, could therefore facilitate the study of CMV congenital infection in human.